Biomimetic Scaffolds Modulate the Posttraumatic Inflammatory Response in Articular Cartilage Contributing to Enhanced Neoformation of Cartilaginous Tissue In Vivo. Issue 1 (28th October 2021) - Bauza‐Mayol, Guillermo; Quintela, Marcos; Brozovich, Ava; Hopson, Michael; Shaikh, Shazad; Cabrera, Fernando; Shi, Aaron; Niclot, Federica Banche; Paradiso, Francesca; Combellack, Emman; Jovic, Tom; Rees, Paul; et al.
Abstract: Focal chondral lesions of the knee are the most frequent type of trauma in younger patients and are associated with a high risk of developing early posttraumatic osteoarthritis. The only current clinical solutions include microfracture, osteochondral grafting, and autologous chondrocyte implantation. Cartilage tissue engineering based on biomimetic scaffolds has become an appealing strategy to repair cartilage defects. Here, a chondrogenic collagen‐chondroitin sulfate scaffold is tested in an orthotopic Lapine in vivo model to understand the beneficial effects of the immunomodulatory biomaterial on the full chondral defect. Using a combination of noninvasive imaging techniques, histological and whole transcriptome analysis, the scaffolds are shown to enhance the formation of cartilaginous tissue and suppression of host cartilage degeneration, while also supporting tissue integration and increased tissue regeneration over a 12 weeks recovery period. The results presented suggest that biomimetic materials could be a clinical solution for cartilage tissue repair, due to their ability to modulate the immune environment in favor of regenerative processes and suppression of cartilage degeneration. Abstract : A biomimetic immune tuning scaffold is implanted in a full‐thickness chondral defect in rabbits. The early inflammatory infiltrates changed in the treated animals resulting in a better cartilage homeostasis at longer timepoints. This work represents the first approach of tuning the inflammatory reaction with a bulk material to achieve a better regeneration in cartilage.